(untitled) (Research, Society and Development, 2025)
Anxiety is a common psychological condition characterized by excessive apprehension and fear that can develop into disorders impairing individuals’ well-being and functionality. Although conventional pharmacological treatments with anxiolytics and antidepressants are effective, they present adverse effects that drive the search for natural alternatives such as phytotherapeutics. This study aims to evaluate the efficacy and safety of the main phytotherapeutics used in the treatment of anxiety based on current scientific literature, in order to contribute to the rational and safe use of these therapies in the pharmaceutical context. An integrative review analyzed studies published between 2014 and 2025, selecting evidence on plants such as Passiflora incarnata, Valeriana officinalis, and Melissa officinalis, which contain bioactive compounds capable of modulating neurotransmitters, especially GABA, promoting anxiolytic effects similar to conventional medications but with a lower risk of side effects and dependence. The results indicate that these phytotherapeutics demonstrate clinical efficacy and a favorable safety profile, highlighting their potential as alternatives or complements in anxiety management, although their use should be guided by trained professionals to ensure proper dosages and avoid drug interactions.